The Quick Exposure Check (QEC) — Inter-rater reliability in total score and individual items. (April 2019) - Oliv, Stefan; Gustafsson, Ewa; Baloch, Adnan Noor; Hagberg, Mats; Sandén, Helena
Abstract: The development of musculoskeletal disorders has been linked to various risk factors in the work environment including lifting heavy loads, machine and materials handling, work postures, repetitive work, work with handheld vibrating tools, and work stress. The Quick Exposure Check (QEC) was designed to assess exposure to work-related musculoskeletal risk factors affecting the back, shoulder/arm, wrist/hand, and neck. We investigated the inter-rater reliability of the summary scores and individual items of the QEC by comparing two simultaneous assessments of 51 work tasks, performed by 14 different workers. The work tasks were mainly "light" to "moderately heavy". For total scores, the level of disagreement for shoulder/arm had a Relative Position of 0.13 (95% CI: 0.02; 0.23) and no statistically significant random disagreement. Percentage agreement was 63–100% for individual items and 71–88% for total score. Weighted Kappa of agreement for the individual items rated by the assessors were −0.94–0.77; highest for back motion, and lowest for wrist/hand position. The Swedish translation of the Quick Exposure Check has moderate to very good inter-rater reliability with fair to slight levels of systematic disagreement. There was no statistically significant random disagreement. Highlights: The inter-rater reliability of the QEC items ranged from substantial to perfect. The inter-rater reliability of the QEC scores ranged from substantial to almost perfect. There were a systematic disagreement on the shoulder/arm and wrist/hand items. The agreement for the individual items were highest for back and lowest for wrist/hand.